The Legal Protection for Female Workers in the Perspective of Islamic Law and Law No. 11 Year 2020 on Job Creation - Ismail Koto; Ida Hanifah (RIRAI Publisher, 2021)
On Monday, 5 October 2020, the Draft Law on Job Creation was ratified by the House of Representatives of the Republic of Indonesia and the manuscript was signed by the government on November 3, 2020. Therefore, since November 3, 2020, the Draft Law on Job Creation promulgated in Law Number 11 Year 2020 on Job Creation. Based on the existing official text, the researcher intended to compare the rights of female workers as regulated in Law Number 13 of 2003 on Manpower with Law Number 11 of 2020 on Job Creation. The research method used in this study was a normative juridical research, with a statutory and conceptual approach, descriptive analytical research specifications, data collection by literature study, and qualitative data analysis. The protection of female workers as referred to in the previous labor law was still valid and was not discussed at all in Law Number 11 of 2020 on Job Creation. Therefore, it could be ascertained that the refusal of workers during the process of the Draft Law on Job Creation is wrong. The article which was amended related to the protection of female workers did not change the substance of the protection of female workers as previously regulated through Law Number 13 Year 2003 on Manpower. The Qur'an has been explained that people need to provide special rights for female workers. Explicitly, there is no verses in the Qur'an that mentioned the word 'special rights for female workers'. However, implicitly, there were general arguments based on the verses in the Qur'an that could be used as a basis for granting this right. Some of the special rights of female workers were implicitly communicated in Islamic teachings.